Shaykh Ahmadou Bamba: A Peacemaker for Our Time - Imtiyaz Yusuf, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
I first heard about Ahmadou Bamba (ca. 1850-1927) thirty-two years ago through the 9-part BBC television series titled The Africans: A Triple Heritage presented by the doyen of Africa and Islam studies, the late Professor Ali Mazrui. The series, which was produced in 1986 was also published in the form of a book. And the name of Ahmadu Bamba has remained in my mind until today. I always wanted to learn more about him. Thanks to Michelle Kimball for this excellent book on Ahmadou Bamba, it is one of the few works on Bamba. I have learned a lot from it, so my hearty congratulations to the author. The good thing about the book is that its chapters are short, crisp and well written, not drowning the reader into a collapsing sleep!